Pengasuhan Anak Terlantar Melalui Program Asah (Asrama Anak Soleh) Di Yayasan Sahabat Yatim : Studi Kasus Yayasan Sahabat Yatim Kota Jakarta Selatan - Lutfiah Difatul Azizah; Muhammad Sahrul (Lembaga Pengembangan Kinerja Dosen, 2024)
Parenting is a way to look after, develop, care for, guide and fulfill children's basic needs, but recently many children have not received optimal care from their families. so that children become vulnerable to abandonment or abandonment. Therefore, an orphanage is the right choice for parents to entrust their children with the aim of being able to fulfill the child's basic needs optimally. The theory used in this research is the parenting theory which contains services, care, guidance, and meeting the needs and elements of the ASAH orphan friend boarding program by facilitating, clothing, food, shelter, education, health, infrastructure, and pocket money and holidays. as well as care from foster parents in orphanages. The results of the research show that the ASAH program has provided optimal care including provision of clothing, food, shelter, education, health, infrastructure, pocket money and holidays so that foster children while they are in the hostel feel very helped because there is a lot of help provided by foster parents. and the Friends Foundation